In-between Translation, Transformation and Contestation: Studying Human Rights Activism as Politics-as-Ruptures in Violent Social Conflicts. (September 2019) - Georgi, F. Richard
How can we study the politics of human rights activism in violent social conflicts? International Relations scholarship has long neglected the ambiguous political relationships between human rights activism and violent social conflicts. Addressing this gap requires new research methodologies that place the focus not on the normative or legal dimensions of human rights, but in how their usage constitutes the political. In this article I argue that using post-foundational discourse theory makes visible 'politics-as-ruptures' that locate the political function of human rights activism precisely in the resistance to representations of violence in conflict discourses. I analyse this political function by asking how activists translate human rights norms, transform conflict discourses, and thereby contest power relations. As examples, the article presents three types of discursive politics that I studied in Colombia. These examples point out further pathways to pose empirical questions about the roles of human rights activism in transforming social conflicts.